ANALYSIS OF FACTORS INFLUENCING FINANCIAL STATEMENT FRAUD WITH EXTERNAL AUDIT QUALITY AS A MODERATING VARIABLE IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX IN 2019-2023 - Nuri Wandasari; Rina Br Bukit; Narumondang Bulan Siregar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze and determine the influence of the elements of the Fraud Hexagon Theory in detecting financial statement fraud in property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2023. Furthermore, this study also aims to determine whether External Audit Quality can be used as a moderating variable in this study. The population in this study was 92 property and real estate companies. Purposive sampling was used to select 29 companies with 145 analysis units. The data used were secondary data derived from company financial reports accessible through the Indonesia Stock Exchange website ( www.idx.co.id ) and related company websites . The results show that Financial Stability partially has a significant positive effect on financial statement fraud and CEO's Educational Background partially has a significant negative effect on financial statement fraud. Meanwhile, Cooperation with Government Projects, Ineffective Monitoring , Change in Auditor , Frequent Number of CEO's Picture have no effect on financial statement fraud. Meanwhile, the results of the Moderated Regression Analysis test in this study indicate that the moderating variable External Audit Quality is only able to moderate the relationship between Financial Stability's influence on Financial Statement Fraud.